Population-Based Sentencing - Eaglin, Jessica M. (2021)
The institutionalization of actuarial risk assessments at sentencing reflects the extension of the academic and policy-driven push to move judges away from sentencing individual defendants and toward basing sentencing on population level representations of crimes and offenses. How have courts responded to this trend? Drawing on the federal sentencing guidelines jurisprudence and the emerging procedural jurisprudence around actuarial risk assessments at sentencing, this Article identifies two techniques. First, the courts have expanded individual procedural rights into sentencing where they once did not apply. Second, the courts have created procedural rules that preserve the space for judges to pass moral judgment on individual defendants. These responses exist in deep tension with policymakers’ goals to shape sentencing outcomes in the abstract. While courts seek to preserve the sentencing process, advocates encourage the courts to manage the population-based sentencing tools. The courts’ response is potentially problematic, as refusal to regulate the tools can undermine criminal administration. However, it presents an underexplored opportunity for courts and opponents of the recent trend toward institutionalizing actuarial risk assessments to jointly create the intellectual and policy-driven space for more fundamental, structural reforms relating to the U.S. criminal legal apparatus. This Article urges the courts and legal scholars to consider these alternatives going forward